Nonlinear Optics - From Solitons to Similaritons 2021
DOI: 10.5772/intechopen.92675
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Responsive Molecular Switches

Abstract: Nonlinear optical (NLO) materials have gained much attention during the last two decades owing to their potentiality in the field of optical data storage, optical information processing, optical switching, and telecommunication. NLO responsive macroscopic devices possess extensive applications in our day to day life. Such devices are considered as assemblies of several macroscopic components designed to achieve specific functions. The extension of this concept to the molecular level forms the basis of molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Due to the evolution of optical communication networks, the search and development of novel compounds with NLO performance have significant importance in improving this field [8,20,21]. For example, frequency optical converters are one of the main components of optical multiplexing [22][23][24]. Another area taking advantage of the optical frequency conversion is the biological field, in which incoherent SHG and third harmonic generation (THG) are being used to improve imaging diagnostics [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the evolution of optical communication networks, the search and development of novel compounds with NLO performance have significant importance in improving this field [8,20,21]. For example, frequency optical converters are one of the main components of optical multiplexing [22][23][24]. Another area taking advantage of the optical frequency conversion is the biological field, in which incoherent SHG and third harmonic generation (THG) are being used to improve imaging diagnostics [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, scientists have paid more attention to molecular photoswitches because they are used in a wide range of fields, such as nonlinear optics (NLO), memory devices, , liquid crystals, electromagnetic switches, synthetic ion channels, , photopharmacology, biological processes, etc. In addition, a significant number of complicated devices, including encoder–decoder, half adder, and logic gates, can be designed based on photoswitches.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, no studies were reported on saturable absorption (SA) and nonlinear refraction (NLR), 37 despite possible applications to optical limiting 38 and switching. 39 Given the unique optical properties of [Pt(N^N)(S^S)] systems and the ongoing search for new NLO materials with third-order nonlinear absorption and refraction properties, the investigation of SA and NLR in platinum diimine-dithiolate complexes was undertaken, and their potential as a new class of third-order NLO materials was assessed. In particular, herein we report on the synthesis, characterization, and thirdorder NLO properties of a series of [Pt(N^N)(S^S)] complexes featuring 5,6-dihydro-1,4-dithiin-2,3-dithiolate (dddt 2− ) or 6,7dihydro-5H-1,4-dithiepin-2,3-dithiolate ( pddt 2− ) as S^S ligands, along with 1,10-phenanthroline ( phen) or 2,2′-bipiridine (bipy) as N^N derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, no studies were reported on saturable absorption (SA) and nonlinear refraction (NLR), 37 despite possible applications to optical limiting 38 and switching. 39…”
Section: Introductionmentioning
confidence: 99%